Emerging role of extracellular vesicles as a senescence-associated secretory phenotype: Insights into the pathophysiology of lung diseases. (April 2018) - Kadota, Tsukasa; Fujita, Yu; Yoshioka, Yusuke; Araya, Jun; Kuwano, Kazuyoshi; Ochiya, Takahiro
Abstract: Aging is a major risk factor for the development of chronic lung diseases such as chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), and lung cancer. A main aspect of aging is the impaired function of maintaining homeostasis in the organs and body, which is associated with cellular senescence. Cellular senescence is recognized as the state of irreversible cell cycle arrest in response to a variety of cellular stresses. Senescent cells are not simply cell cycle-arrested cells; they also affect bystander cells through the secretion of bioactive molecules, termed the senescence-associated secretory phenotype (SASP). Many studies strongly indicate that senescent cells in the lungs are associated with the pathogenesis of age-related lung diseases by releasing SASP factors. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptotic bodies, are released from almost all cell types and are recognized as important mediators of intercellular communication. They have been shown to carry and transfer a wide variety of molecules, such as microRNAs, messenger RNAs, DNA, and proteins, which can contribute to physiological functions and the pathology of various diseases. Increasing evidence suggests that EVs secreted from senescent cells have unique characteristics and contribute to modulating the phenotype of recipient cells similar to SASP factors. Thus, the EVs secreted from senescent cells, namely, senescence-associated EVs, appear to be a novel SASP factor. In this review, we summarize the current knowledge linking senescence-associated EVs to the SASP factor and discuss the roles of these EVs in age-related lung diseases.